Estimate of Dietary Total Antioxidant Capacity of Pregnant Women and Associated Factors - Carvalho, Mariana Rinaldi; Crivellenti, Lívia Castro; Sartorelli, Daniela Saes (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To investigate the dietary total antioxidant capacity (DTAC) of pregnant women, and associated factors.Methods Cross-sectional study conducted with 785 pregnant adult women attended in primary health care centers of Ribeirão Preto, state of São Paulo, Brazil. Two 24-hour dietary recalls were obtained, and the usual intake was estimated through the Multiple Source Method. The DTAC was estimated using the ferric reducing antioxidant power assay. The relationship between the higher DTAC estimate (≥ median of 4.3 mmol/day) and associated factors was investigated using adjusted logistic models with backward selection.Results In total, 25% of the pregnant women were classified as overweight, and 32% as obese. The median (P25, P75) DTAC was 4.3 (3.3–5.6) mmol/day. Through adjusted logistic regression models with backward selection, a higher chance of DTAC estimates above the median among pregnant women aged ≥ 35 years old (2.01 [1.24–3.27]) was verified when compared with younger pregnant women. Women with prepregnancy overweight (0.63 [0.45–0.89]) and obesity (0.59 [0.40–0.88]) presented a lower chance of DTAC estimates above the median when compared with eutrophic pregnant women. A higher DTAC estimate was positively associated with the use of dietary supplements (1.39 [1.03–1.88]), and negatively associated with total dietary energy (0.59 [0.42–0.85]).Conclusion The DTAC estimate over the median was associated with greater age, adequate body weight, use of dietary supplements, and lower energy intake.
Keywords: total antioxidant capacity; pregnant women; diet; antioxidants